Effect of roller dynamic unbalance on cage stress of high-speed cylindrical roller bearing. Issue 9 (19th November 2018) - Cui, Yongcun; Deng, Sier; Ni, Yanguang; Chen, Guoding
Abstract : Purpose: The purpose of this study is to investigate the effect of roller dynamic unbalance on cage stress. Design/methodology/approach: Considering the impact of roller dynamic unbalance, the dynamic analysis model of high-speed cylindrical roller bearing is established. And then the results of dynamic model are used as the boundary conditions for the finite element analysis model of roller and cage to obtain the cage stress. Findings: Roller dynamic unbalance affects the contact status between roller and cage pocket and causes the overall increase in cage stress. The most significant impact on cage stress is roller dynamic unbalance in angular direction of roller axis, followed by radial and axial directions. Smaller radial clearance of bearing and a reasonable range of pocket clearance are beneficial to reduce the impact of roller dynamic unbalance on cage stress; the larger cage guide clearance is a disadvantage to decrease cage stress. The impact of roller dynamic unbalance on cage stress under high-speed condition is greater than that in low-speed conditions. Originality/value: The research can provide some theoretical guidance for the design and manufacture of bearing in high-speed cylindrical roller bearing.